Constructing the (Healthy) Neoliberal Citizen: Using the Walkthrough Method “Do” Critical Health Communication Research - MacLean, Sarah; Hatcher, Simon (Frontiers in Communication, 2019)
Introduction. Since the launch of Web 2.0, we have witnessed a trend towards digitizing healthcare tools for use by both patients and providers. Clinical trials focus on the ways that digital health technologies result in better outcomes for patients, increase access to healthcare and reduce costs. Critical approaches which explore how these technologies result in changes in patient embodiment, power relations and the patient-provider relationship are badly needed. Objective. To provide an instruction case example of how Light, Burgess and Duguay’s (2018) walkthrough method can be mobilized to study apps to address critical health communication (CHC) research questions. Methods. We apply the walkthrough method to the BEACON Rx Platform. In doing, we conduct a detailed technical walkthrough and evaluate the environment of expected use to answer the following questions: How does the platform shape (and how is it shaped by) understandings of what it means to be healthy? Who are its ideal users? How does this impact its environment of expected use? Conclusions. This paper demonstrates the potential contributions of the walkthrough method to critical health communication research, namely how it enables a detailed consideration of how an app’s technical architecture and environment of expected use are embedded with symbolic representations on what it means to be healthy and what practices should be engaged in to maintain “good” health. It also demonstrated that, despite the rhetoric that digital health technologies democratize healthcare, the BEACON Rx platform is a risk monitoring tool by its very design.